2001
DOI: 10.1016/s0002-9440(10)63048-9
|View full text |Cite
|
Sign up to set email alerts
|

Aluminum Chloride Pretreatment of Elastin Inhibits Elastolysis by Matrix Metalloproteinases and Leads to Inhibition of Elastin-Oriented Calcification

Abstract: Calcification of elastin occurs in many pathological cardiovascular diseases including atherosclerosis. We have previously shown that purified elastin when subdermally implanted in rats undergoes severe calcification and aluminum chloride (AlCl(3)) pretreatment of elastin inhibits calcification. In the present study we investigated whether matrix metalloproteinase (MMP) binding to elastin and elastin degradation is prevented by AlCl(3) pretreatment. Subdermal implantation of AlCl(3)-pretreated elastin showed s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(33 citation statements)
references
References 26 publications
0
32
0
1
Order By: Relevance
“…The data published to date do not favor a possible association between Al and aortic stiffness or AoCS, because elastin calcifications and elastolysis by matrix metalloproteinases are prevented by Al chloride. 22,23 Furthermore, several patients with active bone, including those without AoC, had received Al-containing PO 4 binders (Figure 3). The principal novelty of this study concerns the relationships between Ca load, bone activity, and aortic stiffness.…”
Section: Discussionmentioning
confidence: 99%
“…The data published to date do not favor a possible association between Al and aortic stiffness or AoCS, because elastin calcifications and elastolysis by matrix metalloproteinases are prevented by Al chloride. 22,23 Furthermore, several patients with active bone, including those without AoC, had received Al-containing PO 4 binders (Figure 3). The principal novelty of this study concerns the relationships between Ca load, bone activity, and aortic stiffness.…”
Section: Discussionmentioning
confidence: 99%
“…6 Moreover, we have shown that treatment of elastin with aluminum ions before implantation completely abolished elastin calcification by mechanisms that include inhibition of elastolysis by MMPs. 7 These results strongly point to a direct correlation between elastin degradation and calcification. To study mechanisms of elastin calcification in a clinically relevant circulatory model, we adapted an arterial injury model that involves a single periarterial application of a calcium chloride (CaCl 2 ) solution.…”
mentioning
confidence: 87%
“…2. Gels can also be made from elastin, although these are typically used for zymography; 8 fibronectin, 195 which is used as a coating for 2D cell attachment or as a supplement to collagen gels; and hyaluronan, 45 which is often used in in vitro studies of cell-cartilage interactions. Alginate, a naturally occurring polysaccharide, forms a gel when divalent cations are added to the aqueous sodium alginate solution and is often used to study chondrocyte behavior; 83 since it is minimally adhesive for cells, it often has RGD binding sequences added to create a scaffold with specifically selected adhesion properties.…”
Section: Reconstituted Type I Collagen and Fibrin Matricesmentioning
confidence: 99%